Rhetorical criticism and the affective dimension of the biblical text - Martin, Lee Roy (Journal for semitics, 2014)
In the years since James Muilenburg challenged biblical scholars to move beyond form criticism, rhetorical criticism has become an accepted method within Old Testament studies. Biblical scholars, however, have been hesitant to examine the affective argument of biblical rhetoric, what Aristotle called pathos. This article suggests that the biblical documents advocate for certain agendas, and they use both logical and affective proofs to form their arguments. Therefore, what is offered here is a critical approach to examining the affective content of the biblical text, not as a new method, but as one part of the larger hermeneutical strategy.